2006
DOI: 10.1124/jpet.106.110122
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective Effects of l-Carnosine on Ischemia/Reperfusion-Induced Renal Injury in Rats

Abstract: We examined the renoprotective effects of l-carnosine (␤-alanyl-l-histidine) on ischemia/reperfusion (I/R)-induced acute renal failure (ARF) in rats. Ischemic ARF was induced by occlusion of the left renal artery and vein for 45 min followed by reperfusion, 2 weeks after contralateral nephrectomy. In vehicle (0.9% saline)-treated rats, renal sympathetic nerve activity (RSNA) was significantly augmented during the renal ischemia, and renal function was markedly decreased at 24 h after reperfusion. Intracerebrov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 28 publications
3
70
2
1
Order By: Relevance
“…In ischemic acute kidney injury, pharmacological and surgical approaches for inhibiting renal sympathetic nerves prevented ischemia/reperfusion-induced renal dysfunction in rats (4). l-Carnosine prevented elevation of renal noradrenaline outflow and attenuated renal dysfunction induced by ischemia/reperfusion in rats (17). Our present observation indicates that denervation of noradrenaline nerves by DSP-4 attenuates ischemia/reperfusioninduced renal dysfunction (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…In ischemic acute kidney injury, pharmacological and surgical approaches for inhibiting renal sympathetic nerves prevented ischemia/reperfusion-induced renal dysfunction in rats (4). l-Carnosine prevented elevation of renal noradrenaline outflow and attenuated renal dysfunction induced by ischemia/reperfusion in rats (17). Our present observation indicates that denervation of noradrenaline nerves by DSP-4 attenuates ischemia/reperfusioninduced renal dysfunction (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…The renal sympathetic nerve system and circulating catecholamines are considered to be involved in the pathogenesis of AKI because pharmacological blockade of the sympathetic nervous system exerts an efficient protective effect on AKI (Kurata et al, 2006;Sugiura et al, 2008). We recently found that intravenous treatment with GABA (10 and 50 mol/kg) in the ischemic AKI rats efficiently suppressed the enhancement of RSNA during the ischemic period and increased NE overflows after reperfusion (Kobuchi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms underlying ischemia/reperfusion (I/R)-induced renal injury are not fully understood. We found that enhancement of renal sympathetic nerve activity (RSNA) and its consequent effect on norepinephrine (NE) overflow from nerve terminals are considered to be involved in the development of I/R-induced AKI and that RSNA is augmented significantly during renal ischemia in the rats (Fujii et al, 2003;Kurata et al, 2006). In addition, we noted that ischemic AKI is ameliorated by renal denervation or ganglionic blockade and that the effect is accompanied by the suppression of elevated NE levels in the renal vein after reperfusion (Fujii et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Release of pro-inflammatory cytokines, increased expression of endothelial adhesion molecules and of chemotactic factors, as well as infiltration of leukocytes, also play important roles in post-ischemic inflammation, contributing to progression of tissue damage [40]. Several studies have clearly demonstrated that carnosine exerts beneficial effects against I/R-induced organ damage, including the brain [41][42][43]. However, its rapid and complete enzymatic hydrolysis by carnosinases severely limits its potential therapeutic use.…”
Section: Cerebral Ischemia-reperfusion Injurymentioning
confidence: 99%